Cultivation and competition in Colombia: Disentangling the effects of coca price changes on violence - Nicole Stoelinga (Journal of International Development, 2023)
Though evidence indicates the presence of coca increases violence, changes to the price of coca products can have both negative and positive effects on conflict. This study addresses this matter. Using novel data on local prices of coca products, production and supply chains, this study disentangles the returns to employment in the agricultural sector (cultivators) and employment in the criminal sector (guerillas and paramilitaries). I identify each agents' respective exposure to price changes and estimate the effect of such changes on violence. The results show the presence of the opportunity cost effect: an increase in income from coca results in a reduction in violence. This reduction comes with an increase in school attendance for rural households. An increase in the objective prize (OP) leads to more violence. Moreover, guerillas flock to the area that witnesses such an increase, resulting in higher levels of competition which coincides with the timing of the increase in violence. Additionally, increasing expected returns to joining an armed group can lead to higher school dropout rates among children.
Keywords: 300; coca; competition; conflict; income; objective prize